RNAi-mediated knockdown of pituitary tumor- transforming gene-1 (PTTG1) suppresses the proliferation and invasive potential of PC3 human prostate cancer cells - Huang,S.Q. (2012)
Pituitary tumor-transforming gene-1 (PTTG1) is a proto-oncogene that promotes tumorigenesis and metastasis in numerous cell types and is overexpressed in a variety of human tumors. We have demonstrated that PTTG1 expression was up-regulated in both human prostate cancer specimens and prostate cancer cell lines. For a more direct assessment of the function of PTTG1 in prostate tumorigenesis, RNAi-mediated knockdown was used to selectively decrease PTTG1 expression in PC3 human prostate tumor cells. After three weeks of selection, colonies stably transfected with PTTG1-targeted RNAi (the knockdown PC3 cell line) or empty vector (the control PC3 cell line) were selected and expanded to investigate the role of PTTG1 expression in PC3 cell growth and invasion. Cell proliferation rate was significantly slower (28%) in the PTTG1 knockdown line after 6 days of growth as indicated by an MTT cell viability assay (P < 0.05). Similarly, a soft agar colony formation assay revealed significantly fewer (66.7%) PTTG1 knockdown PC3 cell colonies than control colonies after three weeks of growth. In addition, PTTG1 knockdown resulted in cell cycle arrest at G1 as indicated by fluorescence-activated cell sorting. The PTTG1 knockdown PC3 cell line also exhibited significantly reduced migration through Matrigel in a transwell assay of invasive potential, and down-regulation of PTTG1 could lead to increased sensitivity of these prostate cancer cells to a commonly used anticancer drug, taxol. Thus, PTTG1 expression is crucial for PC3 cell proliferation and invasion, and could be a promising new target for prostate cancer therapy.